2002
DOI: 10.1590/s0100-204x2002001200015
|View full text |Cite
|
Sign up to set email alerts
|

Influência de doses de calcário com diferentes relações cálcio: magnésio na produção de matéria seca e na composição mineral da alfafa

Abstract: A acidez dos solos brasileiros, com alumínio em níveis tóxicos e baixa disponibilidade de elementos essenciais, principalmente o fósforo, exige aplicações de calcário e fertilizantes para a adequada utilização agrícola. Este trabalho objetivou avaliar o efeito de quatro doses de calcário calculadas com base no teor de Al3+ trocável do solo e em cinco relações molares de Ca:Mg, na produção de matéria seca e na composição mineral da alfafa. Duas cultivares de alfafa, Flórida 77 e Crioula, foram cultivadas em Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…However, liming does not correct the acidity of the subsoil, and this procedure is not always easy to perform and economically viable [20,21]. In the specific case of alfalfa, liming has been recommended only when it is possible to have soil pH increased to at least 6.0 [22,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, liming does not correct the acidity of the subsoil, and this procedure is not always easy to perform and economically viable [20,21]. In the specific case of alfalfa, liming has been recommended only when it is possible to have soil pH increased to at least 6.0 [22,17].…”
Section: Introductionmentioning
confidence: 99%
“…agrotec., Lavras, v. 29, n. 4, p. 786-794, jul./ago., 2005 Diversos trabalhos (GOMES et al, 2002;HUNTER, 1948;MOREIRA et al, 1999;SIMSOM et al, 1979) mostram que a produção da alfafa não é alterada, em razão das variações nas relações Ca e Mg do calcário. Bull (1986), estudando o efeito da relação K/(Ca+Mg) na produção de matéria seca, observou uma diminuição significativa na absorção de Ca e Mg quando houve elevação nessa relação com o aumento da concentração de K na solução do solo.…”
Section: Introductionunclassified
“…An increase in the K concentration in the soil solution was expected through its addition because increased soil saturation (70%) would make more K available in the soil solution by base fertilization and exchange of K; however, the presence of a large quantity, especially of Ca, in the increasing ratios of cations resulted in a competition Archives of Agronomy and Soil Science 5 with K. Nevertheless, according to Epstein and Bloom (2005), K uptake by the plant is not necessarily worsened by such competition. Likewise, others studies have also found that a decrease in K contents resulted with increasing ratios of Ca:Mg, as in experiments with alfalfa in Oxisols (Gomes et al 2002;Moreira et al 2005), maize in Inceptisols (Pintro et al 2005;Medeiros et al 2008), and peanut in the nutrient solution (Zharare et al 2010). Another preponderant factor is the soil's own capacity for retaining cations like K in accordance with the clay content.…”
Section: Results and Discussion Soilmentioning
confidence: 83%